Turkish Adaptation Study Of Multidimensional Observation Scale For Elderly Subjects - Soygür, Haldun; Duyan, Veli; Hasgül, Ergün; Adibatmaz, Mustafa (Turkish Journal of Family Medicine and Primary Care, 2017)
Introduction: The aim of this study is to adapt the Multidimensional Observation Scale for Elderly Subjects developed by Helmes, Csapo and Short (1987) to Turkish for the aged care workers. The Multidimensional Observation Scale for Elderly Subjects was developed in order to assess the psycho-social functioning of older adults. Methods : The scale has five functional domains, each consisting of eight items. There are a total of 40 items in the scale. The scale was applied to 229 older adults by two social workers who are studying in the field. There were 119 older adults who volunteered to participate in the study among 233 older adults staying in Karabuk Yucel Nursing Home and Kastamonu Nursing and Rehabilitation Center and 110 older adults living with their families in Kastamonu. Results : The Cronbach Alpha values of the functional domains of the scale were found to be .89 for self-care; .85 for disorientation; .80 for depression/anxiety; .77 for irritability, and .87 for withdrawal, respectively. As a result of the confirmatory factor analysis, it was determined that the distribution of the items in the Multidimensional Observation Scale for Elderly Subjects to the subscales was similar to the distribution in the original scale. Furthermore, reliability values of the scale and its subscales are adequate. Conclusion : It is thought that the Turkish form of the scale can be used to evaluate multidimensional and determine the cognitive, psychological and social functionings of older adults who are in institutional care or live with their families in Turkey. Giris : Bu calismanin amaci, Helmes, Csapo ve Short (1987) tarafindan gelistirilmis olan Yasli Bireyler Icin Cok Boyutlu Gozlem Olcegini yaslilik alaninda calisanlar icin Turkceye uyarlamaktir. Yasli Bireyler Icin Cok Boyutlu Gozlem Olcegi, psikososyal acidan ve yaslilarin islevselliklerini cok yonlu degerlendirmek amaciyla gelistirilmistir. Yontem : Olcek her biri sekiz maddeden olusan bes islevsel alana sahiptir. Olcekte toplam 40 madde bulunmaktadir. Olcek, Karabuk Yucel Huzurevi ve Kastamonu Huzurevi ve Yasli Bakim Rehabilitasyon Merkelerinde kayitli olarak yasayan toplam 233 bireyden calismaya katilmaya gonullu olan 119’u ve Kastamonu ilinde ailesi ile yasayan 110’u olmak uzere toplam 229 yasli bireye, alanda calisan iki sosyal hizmet uzmani tarafindan uygulanmistir. Bulgular : Olcegin islevsel alanlarinin Cronbach Alpha degerleri sirasiyla oz-bakim icin 0,89; yonelim bozuklugu icin 0,85; depresif/kaygili duygudurum icin 0,80; huzursuzluk verici davranis icin 0,77 ve toplumdan uzaklasma icin 0,87 olarak bulunmustur. Yasli Bireyler Icin Cok Boyutlu Gozlem Olcegini olusturan maddelerin alt olceklere dagiliminin dogrulayici faktor analizi sonucunda orijinal olcekteki dagilimla benzer oldugu saptanmistir. Ayrica olcegin butunune ve alt olceklerine ait guvenirlik degerleri yeterli duzeydedir. Sonuc : Olcegin Turkce formunun Turkiye’de kurum bakim hizmeti alan ya da ailesiyle birlikte yasayan yasli bireylerin bilissel, psikolojik ve sosyal islevselliklerini belirlemede ve cok boyutlu degerlendirmede kullanilabilecegi dusunulmektedir.
Keywords: Elderly; functionality; multidimensional observation for elderly subjects; MOSES; 3. Good health